Occurrence of Gastrointestinal Parasites in Camels in the Tianshan Mountains Pastoral Area in China - Guowu, Zhang (J Vet Res, 2020)
INTRODUCTION: Gastrointestinal parasites are some of the most common pathogens which are seriously harmful to the camel’s health. The infection status of gastrointestinal parasites in camels (Camelus bactrianus) in the Tianshan Mountains pastoral area in China is still unclear. The aim of this study was to investigate the species and infection intensity of gastrointestinal tract parasites in local camels. MATERIAL AND METHODS: A total of 362 fresh faecal samples were collected and examined for parasite eggs using the saturated saline floating and natural sedimentation method. The parasite eggs were subjected to morphological and molecular examination and identification, and the infection rate and mean intensity of the parasites were analysed. RESULTS: A total of 15 gastrointestinal tract parasite species’ eggs were identified, with a detection rate of 100%. Ostertagia spp. (100%) and Trichostrongylus spp. (98.1%) were dominant. Camels were often coinfected by 5–14 species. The average number of eggs per gram of faeces was higher for Ostertagia spp. (298), Haemonchus contortus (176) and Nematodirus spp. (138). The number of species of parasites infecting young camels was significantly lower than that of adult camels, but the infection intensity in young camels was significantly higher. CONCLUSION: Gastrointestinal parasites were highly prevalent in camels from the Tianshan Mountains pastoral area in China. This finding provides important epidemiological data for the prevention and control of associated infections in camels.